Opinions of school administrators on school effectiveness after the earthquakes - Orhan, Mustafa; Demırkol, Murat; Karagözoğlu, Ahmet Alper (My University, 2025)
Schools, as educational institutions, have played a crucial role as shelters during earthquake disasters and have subsequently contributed to the normalization of life through educational and training activities. In this context, the role of school administrators working in these institutions has become prominent. Effective use of human and material resources by school administrators is essential for school effectiveness. This qualitative phenomenological study aimed to explore the experiences, opinions, and recommendations of school administrators regarding school effectiveness after earthquakes. The study involved 17 school administrators selected using purposeful sampling method from those working in Elazığ during the 2023-2024 academic year. Data were collected through semi-structured interviews and analyzed using content analysis. Findings revealed that school administrators made efforts to enhance disaster awareness among staff after earthquake disasters. Guidance services provided support, particularly to students facing psychological issues. While some participants found the support from superiors sufficient, many reported deficiencies in this regard. It was evident that earthquakes had physical, administrative, and educational impacts on schools. The study also highlighted a lack of disaster awareness among administrators, teachers, and students, negatively affecting educational activities.
Keywords: School administrators; School effectiveness; disaster awareness